THE PHENOMENON OF RESILIENCE AS A RESOURCE FOR STUDENTS’ EDUCATIONAL SUCCESS - Юлдашева Makhliyo; Saminjonova, Zulaykho (MMIT Proceedings, 2023)
The concept of resilience denotes a separately significant phenomenon of the human psyche, which develops according to certain genetic patterns, is a multicomponent personal education that affects the actualization of various human properties in situations of life stress. The article is devoted to resilience as a personal characteristic that explains the ability to resist the negative consequences of stressful circumstances. The theory of resilience is analyzed, a review of its research, the development of a diagnostic tool, and a brief discussion of the prospects for further application of this construct. The materials of an empirical study obtained on a sample of students of the Ferghana State University are presented